Ruthenium bipyridyl tethered porous organosilica : a versatile, durable and reusable heterogeneous photocatalyst - Jana, Avijit (2015)
A versatile heterogeneous photocatalysis protocol was developed by using ruthenium bipyridyl tethered porous organosilica (Ru-POS). The versatility of the Ru-POS catalyst in organo-photocatalysis was explored by (i) oxidative aromatization of Hantzsch ester, (ii) reductive dehalogenation of alkyl halides, and (iii) functional group interconversion (FGI) of alcohols to alkyl halides.